APPLYING TEAM QUIZ STRATEGY TO IMPROVE STUDENT LEARNING OUTCOMES IN ARABIC LANGUAGE (AN EXPERIMENTAL STUDY OF THE FIRST-YEAR FEMALE STUDENTS AT THE ISLAMIC STATE INSTITUTE OF LHOKSEUMAWE): تطبيق إستراتيجية فريق المسابقة لترقية نتائج تعلم اللغة العربية (دراسة تجريبية لطالبات الصف الأول بمعهد الجامعة الإسلامية الحكومية لهؤسماوي) - Salmawati, Salmawati (Al Mihwar: Jurnal Pendidikan Bahasa Arab dan Kebahasaan, 2023)
This article is entitled Implementation of the Team Quiz Strategy to improve student learning outcomes in Arabic language lessons." The researcher chose this title based on learning activities in class 1 of Makhad Jami'ah IAIN Lhokseumawe which was considered less efficient because the number of students studying in one class was more than 50 students. This makes it difficult for teachers to guide each individual so that it influences learning outcomes, and there is a lack of strong motivation within the students themselves to learn the Arabic Language. This research aims to determine the effectiveness of the Team Quiz Strategy to improve Arabic language learning outcomes in class 1 of Makhad Jami'ah IAIN Lhokseumawe. The method used in this research is quantitative research with experimental studies, with a population of all female students in class 1 of Makhad Jami'ah IAIN Lhokseumawe and the sampling technique used purposive sampling. The data collection technique in this research uses pre-test and post-test and the data analysis technique uses t-test. Based on the results of the t test, it can be concluded that the implementation of the Team Quiz strategy is effective in improving Arabic language learning outcomes in class 1 Makhad Jami'ah IAIN Lhokseumawe, this is shown from the results of t count>t table (2.70>2.00) with a significance level of 5% or 0.05 and the sig value is <0.05, which means that the learning outcomes in the experimental class are significantly higher than the learning outcomes in the control class.